Fasal pengecualian dalam kontrak jualan barang : halangan tuntutan pengguna - Sakina Shaik Ahmad Yusoff, (Fakulti Undang - Undang, 2002)

(untitled)
Most customers faced with contract containing ‘small print’ do not know what it contains or understand the effect of the clauses. Exclusion clauses may deprive a consumer of certain specific rights which social policy requires that he should have. Very often they are introduced in ways which results in consumers remaining ignorant of heir presence. In a contract of sale of goods, consumers are being confronted with an even worse position. The Sale of Goods Act 1957, the primary source of the law of sale of goods in Malaysia, allows the seller to avoid all the statutory implied conditions imposed on them under section 14 – 17 by merely inserting a clause to the effect. Nevertheless the harshness caused by such clauses has to a certain extent been lessened by the Consumer Protection Act 1999. This article aims to look at the meaning, function, the rule of interpretation and application of exclusion clauses in the context of consumer sale of goods. Readers will then be exposed to some suggested legislative reforms in this area